TECHNIQUES OF LAW COMMUNICATION IN ADMINISTRATIVE DECISIONS AND ORDERS - LIZISOWA, Maria Teresa (Comparative Legilinguistics, 2018)
The article is a linguistic lecture on mutual relations between legal language and legislative language on the semantic, syntactic, pragmatic and stylistic planes. The author analysed decisions and official regulations with regard to the status of language as well as the linguistic understanding of communication. A decisive official act is a testimony of the primary reading of the text of a legislative act by an official, fulfilling the role of an interpreter and a decision maker in applying law. He fulfils a duty imposed on him by the norm of competence, verbalised in principles of legal acts. In the process of organizing a legal text, he makes use of the rules of language, according to both the studied and the statutorily recommended rules of the interpretations of law. Through evoking the content of legal articles in official documents, therefore through concretization of legal norms in the process of reception, the legal meanings and contexts undergo a certain kind of assimilation by an official-interpreter. Later, they become adapted in corresponding legal situations, and finally, as a consequence, a process of universalization of knowledge about the established law takes place, because an official-decision maker inscribes his personal knowledge of the legislative content into a specific legal reality of his own community.